2017
DOI: 10.1111/bjso.12211
|View full text |Cite
|
Sign up to set email alerts
|

‘I didn't mean that: It was just a slip of the tongue’: Racial slips and gaffes in the public arena

Abstract: Speech errors, slips, and gaffes made in the public arena that are perceived to be either implicitly or explicitly racially offensive often result in significant social consequences to the responsible speaker and generate public controversy. The current research, informed by conversation analysis and discursive psychology, examines how speakers manage such troubles-in-speaking in public settings. The sample of naturalistic data includes five such instances and related apologies sourced from YouTube and news we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Moreover, psychological research has identified likely social functions served by derogatory language that can be grouped into five main categories: prejudice perpetuation; maintenance of status hierarchies; legitimization of violence against outgroups; norm and role compliance; and ingroup cohesion. We are not claiming that people engage in language-based discrimination with these aims in mind but, rather, that these are the primary social functions and consequences of disparaging language, which may well operate outside of people’s awareness and intention (see Burford-Rice & Augoustinos, 2017). To illustrate these functions, we will briefly and selectively review the relevant literature.…”
Section: The Social Functions Of Derogatory Languagementioning
confidence: 99%
“…Moreover, psychological research has identified likely social functions served by derogatory language that can be grouped into five main categories: prejudice perpetuation; maintenance of status hierarchies; legitimization of violence against outgroups; norm and role compliance; and ingroup cohesion. We are not claiming that people engage in language-based discrimination with these aims in mind but, rather, that these are the primary social functions and consequences of disparaging language, which may well operate outside of people’s awareness and intention (see Burford-Rice & Augoustinos, 2017). To illustrate these functions, we will briefly and selectively review the relevant literature.…”
Section: The Social Functions Of Derogatory Languagementioning
confidence: 99%
“…These are that discrimination is (1) morally wrong and irrational; (2) performed by a particular kind of problematic identity (uneducated, isolated, and pathological); (3) deliberate and intended by the actor. Consequently, an act is not discrimination when it is (4) based on rational and objective realities; and (5) not intended to cause harm (Andreouli, Greenland, & Howarth, 2016; Augoustinos & Every 2007; Burford-Rice & Augoustinos, 2017; Capdevila & Callaghan, 2007; Every & Augoustinos, 2007; Figgou & Condor, 2006; Goodman & Rowe, 2014; Greenland & Taulke-Johnson, 2017; Howarth, 2009; Kadianaki, 2014; Kirkwood, McKinlay & McVittie, 2013; Moore & Greenland, 2018; Sommers & Norton, 2006; Swim, Scott, Sechrist, Campbell, & Stangor, 2003; Wilkins, 2012).…”
Section: ‘Discrimination’ As a Construct In Everyday Social Practicementioning
confidence: 99%
“…The aim of the present analysis was to explicate instances of parliamentary debate in which being a MP was made a relevant and consequential membership category (Sacks, ). We analysed the data using an approach (Burford‐Rice & Augoustinos, ; Stokoe & Wallwork, ) that draws upon the method of membership categorization analysis (Sacks, ), and principles and tools derived from discursive psychology (Edwards, ; Edwards & Potter, ) and rhetorical psychology (Billig, ). Following membership categorization analyses, we focus on the ways in which politicians evoked the category of MP and drew upon recognized category‐bound features (Hester & Eglin, ; Lepper, ; Sacks, ) to address Wilders’ (anti‐immigrant) statements.…”
Section: Materials and Analytical Approachmentioning
confidence: 99%